The defiant and the compliant: how does procedural justice theory explain ethnic minority group postures toward police? - Sargeant, Elise (Policing and society, 2021)
Understanding public dispositions to defy police is important for police practice. Citizen defiance can result in arrest, injury or even death. The current study examines the antecedents of ‘defiant’ and ‘compliant’ motivational postures among a sample of 1,480 ethnic minority group members. Developing a better understanding of defiant and compliant postures is important when studying ethnic minority groups who may be more likely to defy police compared to majority populations. Three competing theoretical models incorporating social identity and procedural justice are tested: the group value, group engagement and uncertainty management models. Each model variously seeks to explain how and why procedural justice may foster or reduce compliant or defiant postures toward police among ethnic minority group members. Upon testing these models we find that the efficacy of procedural justice varies depending on which posture is predicted.